Mesenteric desmoid fibromatosis entrapping metastatic urothelial carcinoma: a unique collision tumor or fibromatosis-like variant? - Lorenzo Gitto; Thomas Vandermeer; David J. Lubin; Daniel J. Zaccarini (BMC, 2022)
Abstract A collision tumor is a neoplastic lesion comprised of two or more distinct cell populations with distinct borders. Desmoid fibromatosis (DF) is a rare musculoaponeurotic tissue tumor that grows deep in the connective tissue and shows locally aggressive behavior. Only two cases of collision tumors with desmoid fibromatosis are reported in the English literature, albeit papillary thyroid carcinoma with desmoid fibromatosis-like stroma is regarded as a variant rather than a collision tumor. We present a unique case of collision tumor with desmoid fibromatosis surrounding intra-abdominal metastasis from urothelial carcinoma. A 65-year-old white male with history of bladder and left renal pelvis high-grade papillary urothelial carcinoma status post-nephrectomy was found to have a small bowel obstruction due to a soft tissue mass. Histology of the mass showed multiple matted lymph nodes with metastatic urothelial carcinoma admixed with a proliferation of spindle cells positive for nuclear beta-catenin, consistent with desmoid fibromatosis. While the prior surgical site likely acted as a nidus for development of desmoid fibromatosis, we also hypothesize that a dysregulation of beta-catenin signaling pathways within the cancer cells might have attributed to the spindle cell proliferation in the stroma surrounding the tumor. Our case emphasized the importance of clinical suspicion of desmoid fibromatosis in patients with metastatic cancer, requiring a prompt diagnosis and treatment to decrease the risk of complications and local recurrence.